Assessing the Predictive Ability of Metabolic Syndrome-ATP III for Survival and Complications in Patients with Metastatic Spinal Cord Compression. (16th November 2020) - Fatima, Nida; Shin, John H
Abstract: INTRODUCTION: Metabolic Syndrome (MetS) is a global epidemic disorder, especially in the western capitalistic economic development model METHODS: Patients with MSCC presented at an academic tertiary care hospital from 2011 to 2018 were identified through retrospective chart review. Patients were categorized into MetS-ATP III (42.9%, n = 51) if they meet 3 or more of the following criterion: waist circumference (men >102 cm and women >88 cm), triglycerides (≥150 mg/dl), high density cholesterol (men <40 mg/dl and women <50 mg/dl), blood pressure (≥130/≥85 mmHg) and fasting glucose (≥110 mg/dl). Cox-Multivariate proportional hazards regression model was computed to determine the association of MetS-ATP III with postoperative outcomes. Kaplan-Meier survival curve with the log-rank test was used to visually illustrate the differences in survival between MetS patients. RESULTS: Statistical analysis included 119 patients (median age: 67 years; 63% males), with a median survival of 14 months (95%CI: 1–28.2 months, P  = .01). All-cause mortality and complications were 62.2% (n = 74) and 22.7% (n = 27) in our cohort respectively. Patients with MetS-ATP III had 1.74-folds higher risk of mortality at last follow up evaluation (HR: 1.74, 95%CI: 1.07-2.81, P  = .02), after adjusting for age, sex, tumor histology and spine instability neoplastic score (SINS). Overall complication rates were significantly higher among patients with MetS (HR: 4.06, 95%CI: 1.68-9.82, P  = .002). Furthermore, the patients with MetS had a higher probability of impaired wound healing (HR: 3.85, 95%CI: 1.57-9.40, P  = .003) and thrombotic disorders (HR: 5.56, 95%CI: 1.63-19.0, P  = .006), adjusted for age, sex, tumor histology and SINS. CONCLUSION: MetS-ATP III analysis in patients with MSCC who underwent DS was effective in identifying patients at higher risk for shorter survival and more complications. However, further prospective studies are needed to validate our results.